Innovative activity of industrial enterprises: exogenous and endogenous factors - N. V. Lyasnikov; N. T. Uspenskaja (Путеводитель предпринимателя, 2020)
In this article the main approaches to classification of factors of innovative activity of the modern industrial enterprises are stated. In article the author ’s concept of typification and specific variety of the specified factors is stated, and also specifics of their influence on a competitive strategically sustainable development of the industrial enterprises in the conditions of new cognitive economy are defined.